Therapeutic Hypothermia Treatment for an Infant with Hypoxic-Ischemic Encephalopathy and Gastroschisis: A Case Report - Flores-Fenlon, Nicole; Shafer, Grant; Awan, Saeed; Ahmad, Irfan (American Journal of Perinatology Reports, 2023)
Gastroschisis is a congenital, typically isolated, full-thickness abdominal wall defect in which the abdominal contents, usually only the small intestine, remain outside the abdominal cavity. It is commonly detected on fetal ultrasonography, and has generally excellent survival and outcomes, though these can be decreased in cases of complicated gastroschisis. We present the case of a female infant with a prenatal diagnosis of gastroschisis who required a prolonged and complex resuscitation after delivery. In addition to her gastroschisis, she presented with a history and physical examination consistent with severe hypoxic-ischemic encephalopathy and was treated with therapeutic hypothermia (TH) without further compromise to her bowel. In addition, careful consideration of neuroprotection, fluid status, bowel viability, and hemodynamics were undertaken in her care. She was discharged home on full enteral feeds, with only mild language and gross motor delays at 6 months of age. To our knowledge, there are no reports in the literature of the use of TH in the setting of unrepaired simple gastroschisis.
Keywords: gastroschisis; hypoxic-ischemic encephalopathy; therapeutic hypothermia; neonatal intensive care unit; pediatric surgery